EDITORIAL - Basto Sáez, Manuel Jesús (2022)
Siglo XXI, magazine for the dissemination of scientific-technological knowledge, spokesman of the work and thinking of the university community of the National University of Huancavelica, in its eagerness to serve the academic population, constitutes first class material to communicate the creation, qualification and updating of knowledge related to the various scientific and/or technological disciplines generated by academics specialized in the dimensions of health, engineering, law, business sciences and education sciences, with the purpose of contributing to the understanding and use of knowledge related to their specialty.We are aware that it is extremely difficult to separate academic expression from scientific knowledge related to health sciences. However, we have selected a set of scientific articles that in any account of science and/or technology would be recognized as important from the perspective of the fecundity of the debates and research that they have been provoking. Thus, for example, aspects related to self-care and occupational risk in the nursing professional, the characterization of safety in patient care from the nursing professional's perception, or the response to Covid-19 in primary care nurses, or other problems that are the subject of research. Likewise, it is necessary to emphasize that the present edition of Siglo XXI is, to show our persevering spirit in the communication of the tasks of investigative nature of the professionals in health sciences, thinking in function of the needs of the members of the academic community of the regional, national and international scope.In addition, it is pertinent to note that science in the current historical moment has become the core of contemporary culture and the dynamics of technology, since the purpose of science is to indirectly control the economic dimension of a given socio-political and cultural context. For this reason, if it is necessary to internalize an adequate and coherent idea of society and of man as a being endowed with reasoning, it is important to study, understand and disseminate the intellectual production of a scientific nature.Finally, we persist in inviting the persons or institutions interested in disseminating the works elaborated, related to scientific and/or technological disciplines to send us, in the form of a scientific article, whose gesture we will be highly recognized and from now on, we are ready to publish them in the present instrument of diffusion of scientific and/or technological knowledge.THE EDITOR.